2020
DOI: 10.21315/mjms2020.27.5.8
|View full text |Cite
|
Sign up to set email alerts
|

First Parental Concerns and Age at Diagnosis of Autism Spectrum Disorder: A Retrospective Review from Malaysia

Abstract: Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder. This is the first study to examine first parental concerns in ASD in Malaysia. We examined: i) age and type of first parental concerns (AOC); ii) association between AOC and severity; iii) time lag between AOC and diagnosis; and iv) factors associated with diagnostic delay. Methods: Medical records of 366 patients (aged 1–18 years) with ASD, at the Developmental Paediatrics Clinic of University of Malaya Medical Centre (UMMC), Kuala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Specifically, (Koegel and Schreibman, 1976 ) reported on a child with ASD who appeared to be deaf for complex sounds (white noise) but responded to environmental sounds at normal thresholds. A review of 1st birthday home videos revealed that children with ASD often failed to orient to their name being called (Osterling and Dawson, 1994 ), have a clear preference for noise or non-verbal sounds over speech and vocalizations (Klin, 1991 , 1993 ) or frank impairment for speech sounds (Ceponiene et al, 2003 ; Jeste and Nelson, 2009 ; Bidet-Caulet et al, 2017 ; Jayanath and Ozonoff, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, (Koegel and Schreibman, 1976 ) reported on a child with ASD who appeared to be deaf for complex sounds (white noise) but responded to environmental sounds at normal thresholds. A review of 1st birthday home videos revealed that children with ASD often failed to orient to their name being called (Osterling and Dawson, 1994 ), have a clear preference for noise or non-verbal sounds over speech and vocalizations (Klin, 1991 , 1993 ) or frank impairment for speech sounds (Ceponiene et al, 2003 ; Jeste and Nelson, 2009 ; Bidet-Caulet et al, 2017 ; Jayanath and Ozonoff, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2 , 13 of the 30 included studies were conducted in upper-, middle-, and lower-income countries. 18–29 The other 16 studies were conducted in high-income countries, including six in the US, 20 , 30–34 four in the United Kingdom (UK), 35–37 two in Spain, 21 , 22 two in Germany, 38 , 39 two in Australia, 23 , 24 and one in Saudi Arabia. 40
Figure 2 Distribution of means according to the level of development of the countries in the studies.
…”
Section: Resultsmentioning
confidence: 99%
“… 33 However, in the Venezuelan study, higher social and economic status and higher parental education levels were associated with earlier diagnosis. 48 Whereas, Jayanath and Ozonoff’s 18 Malaysian study showed that sociodemographic factors were associated with a later diagnosis. One study found that Hispanic children in the US tended to receive services for ASD later than non-Hispanic White children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations